2012
DOI: 10.1021/ac3003227
|View full text |Cite
|
Sign up to set email alerts
|

Disposable Immunochips for the Detection of Legionella pneumophila Using Electrochemical Impedance Spectroscopy

Abstract: The rapid diagnosis of Legionellosis is crucial for the effective treatment of this disease. Currently, most clinical laboratories utilize rapid immunoassays that are sufficient for the detection of Legionella serogroup 1, but not other clinically relevant serogroups. In this report, the development of a disposable immunochip system is described in connection with electrochemical impedance spectroscopy and fluorescence microscopy. The immunochips were prepared by covalently immobilizing fluorophore-conjugated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 20 publications
(21 reference statements)
0
42
0
1
Order By: Relevance
“…[36][37][38][39] Previously, voltammetric techniques have been employed to study the antioxidant ability of resveratrol. Corduneanu and coworkers 40 reported that, the antioxidant activity of resveratrol was dependent on the pH of the supporting electrolyte and was shown to be a moderate strength antioxidant with irreversible oxidation processes.…”
mentioning
confidence: 99%
“…[36][37][38][39] Previously, voltammetric techniques have been employed to study the antioxidant ability of resveratrol. Corduneanu and coworkers 40 reported that, the antioxidant activity of resveratrol was dependent on the pH of the supporting electrolyte and was shown to be a moderate strength antioxidant with irreversible oxidation processes.…”
mentioning
confidence: 99%
“…Other conventional detection tests use direct immunofluorescence assay, urinary antigen test, serology testing or polymerase chain reaction [8]. However, these methods have turnaround times measurable in several hours to days, are expensive, technically demanding, and limited in their detection of different serogroups [2]. Therefore, sensitive and rapid detection methods for the sensitive and selective detection of this target bacterium in water systems are of great interest.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Electrochemical immunosensors have attracted great interest because they combine the high selectivity provided by immunological species with the high sensitivity achieved with modern electrochemical techniques [2,[5][6][7] and have the advantages of rapid analysis time, ability of detecting analytes in complex biological media with high specificity and sensitivity and a relatively inexpensive cost compared to other immunoassay methods. In particular, two M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 electrochemical immunosensors have been reported for L. pneumophila determination [2].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 2 more Smart Citations